Temperature Dependent Seed Germination of Dalbergia nigra Allem (Leguminosae) - Ferraz-Grande, Fernanda G. A. [UNESP]; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2001)
A germinação de sementes de Dalbergia nigra Allem, comumente conhecida como jacarandá-da-Bahia, caviúna, jacarandá, uma espécie em extinção, foi estudada e determinamos a temperatura ótima de 30,5° C. A espécie apresenta uma ampla faixa de temperatura onde a germinação ocorre e a luz branca não influenciou o processo. A análise da cinética da germinação de sementes confirma a germinação não sincronizada acima e abaixo da temperatura ótima de germinação. A semente insensível à luz e a germinação também em altas temperaturas indicam que D. nigra pode ocorrer tanto na sombra da vegetação bem como em clareiras.

The germination of endangered species Dalbergia nigra was studied and 30.5° C was found as optimum temperature, although the species presented a broad temperature range where germination occurs and light had no effect. The analysis of kinetics of seed germination confirmed the asynchronized germination below and above the optimum temperature. The light insensitive seed and germination also at high temperatures indicated that D. nigra could occur both in understories and gaps where the mean temperature was high.
Keywords: Dalbergia nigra; endangered species; seed germination; temperature